Apakah Self Efficacy Memediasi Pengaruh Kompetensi, Mindset, Pendidikan terhadap Kesempatan Kerja Lulusan Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang ? - Yahya, Rifan; Utami, Ratih Hesti; Setiawati, Ira (Jurnal Ilmiah Aset, 2023)
The research was conducted aiming to determine the effect of mindset competency, education through self-efficacy as a mediating variable on job opportunities for graduates of the Faculty of Economics and Business, PGRI University Semarang. The research method used is quantitative descriptive analysis. The population of this study used a saturated sample, meaning that the entire population consisted of 118 graduates. Data obtained through the telegram group "management carrier project". Data analysis in this study used the SmartPLS version 3 program. The data analysis technique used was the Structural Equation Modeling (SEM) equation model. The results of the analysis and discussion show that competency variables affect employment opportunities, mindset influences employment opportunities, education influences employment opportunities, self-efficacy influences employment opportunities, competence influences employment opportunities mediated by self-efficacy, mindset does not affect employment opportunities which is mediated by self-efficacy, education influences employment opportunities which is mediated by self-efficacy of graduates of the Faculty of Economics and Business, PGRI Semarang University.